Cost-effectiveness of an Environmental Cleaning Bundle for Reducing Healthcare-associated Infections. (30th July 2019) - White, Nicole M; Barnett, Adrian G; Hall, Lisa; Mitchell, Brett G; Farrington, Alison; Halton, Kate; Paterson, David L; Riley, Thomas V; Gardner, Anne; Page, Katie; Gericke, Christian A; Graves, Nicholas
Abstract: Background: Healthcare-associated infections (HAIs) remain a significant patient safety issue, with point prevalence estimates being ~5% in high-income countries. In 2016–2017, the Researching Effective Approaches to Cleaning in Hospitals (REACH) study implemented an environmental cleaning bundle targeting communication, staff training, improved cleaning technique, product use, and audit of frequent touch-point cleaning. This study evaluates the cost-effectiveness of the environmental cleaning bundle for reducing the incidence of HAIs. Methods: A stepped-wedge, cluster-randomized trial was conducted in 11 hospitals recruited from 6 Australian states and territories. Bundle effectiveness was measured by the numbers of Staphylococcus aureus bacteremia, Clostridium difficile infection, and vancomycin-resistant enterococci infections prevented in the intervention phase based on estimated reductions in the relative risk of infection. Changes to costs were defined as the cost of implementing the bundle minus cost savings from fewer infections. Health benefits gained from fewer infections were measured in quality-adjusted life-years (QALYs). Cost-effectiveness was evaluated using the incremental cost-effectiveness ratio and net monetary benefit of adopting the cleaning bundle over existing hospital cleaning practices. Results: Implementing the cleaning bundle cost $349 000 Australian dollars (AUD) and generated AUD$147 500 in cost savings. Infections prevented under the cleaning bundle returned a net monetary benefit of AUD$1.02 million and an incremental cost-effectiveness ratio of $4684 per QALY gained. There was an 86% chance that the bundle was cost-effective compared with existing hospital cleaning practices. Conclusions: A bundled, evidence-based approach to improving hospital cleaning is a cost-effective intervention for reducing the incidence of HAIs. Abstract : We evaluated the cost-effectiveness of an environmental cleaning bundle for preventing healthcare-associated infections. Compared with current hospital cleaning practices, bundle implementation was cost-effective at $4684 per quality-adjusted life-years based on predicted reductions in Staphylococcus aureus bacteremia and vancomycin-resistant infection rates.